Cone-beam computed tomography application in age estimation (Research, Society and Development, 2022)
Age estimation is a fundamental process in Forensic Science. Different methods of dental age assessment have been developed to estimate the chronological age of living and dead humans, including the use of 3D images obtained from Cone-beam Computed Tomography (CBCT). The aim of this study was to analyze, through a literature review, the use of CBCT for age estimation. For this purpose, complete scientific articles published in national and international journals were used. CBCT proved to be effective during age estimation, in dental and bone analyses. However, the chronological age, the level of dental development, as well as the different groups of teeth seem to influence the analyses, determining a higher or lower level of reliability in the presumption of age. CBCT exams are an excellent alternative for analyzing both dental and bone tissues, contributing significantly to age estimation.